2006
DOI: 10.1177/0192636506295392
|View full text |Cite
|
Sign up to set email alerts
|

Technology Standards for School Administrators: An Analysis of Practicing and Aspiring Administrators' Perceived Ability to Perform the Standards

Abstract: This study investigated practicing and aspiring school administrators' perceived level of proficiency related to the Technology Standards for School Administrators adopted by the International Society for Technology in Education. Based on the mentor-mentee relationship, the study found there were no significant differences between mentors and mentees in their perceived ability to meet any of the Technology Standards for School Administrators. However, there was a significant difference between mentors and ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 3 publications
2
15
1
2
Order By: Relevance
“…As society increases as a technology-rich environment, school leaders are faced with how to support the integration of technology into meaningful learning activities and how to evaluate the use of technology within their schools (Yu & Durrington, 2006). MacNeil and Delafield (1998) found that when administrators act as technology leaders, the teachers and students integrate and use technology more successfully.…”
Section: Resultsmentioning
confidence: 99%
“…As society increases as a technology-rich environment, school leaders are faced with how to support the integration of technology into meaningful learning activities and how to evaluate the use of technology within their schools (Yu & Durrington, 2006). MacNeil and Delafield (1998) found that when administrators act as technology leaders, the teachers and students integrate and use technology more successfully.…”
Section: Resultsmentioning
confidence: 99%
“…(Yu & Durrington, 2006). The characteristics that should be displayed by a technological leader are further explained as follows (Hacıfazlıoğlu et al, 2010): visionary leadership, learning culture in digital age, perfectionism in professional practice, systematic development, digital citizenship.…”
Section: Technology Leadership and Self-efficacymentioning
confidence: 99%
“…First, a significant body of research focuses on leaders. Topics of analysis include the goals of technology use – educational and administrative goals (Afshari et al, 2008); development of collaborative abilities , creation of an organizational culture, and search for common objectives (Hsiao & Chang, 2011; Sheppard, 2003); importance of directors’ knowledge of the integration of educational technology (Shattuck, 2010); type of leadership for implementing ICT successfully in education (Hadjithoma-Garstka, 2011; McGarr & Kearney, 2009; Ng, 2008); level of performance of the director’s technology-related functions (Fisher & Waller, 2013; Yu & Durrington, 2006); gender differences , academic level, leaders’ experience in supply, technological competence, and use of educational technologies (Alkrdem, 2014; Drake, 2015); directors’ training in technology use (Raman et al, 2014; Sheppard, 2003); leaders’ beliefs , perception, and view of ICT and school culture (Chang et al, 2008); competence to develop technology leadership behavior (Thomas et al, 2013); capability to assume the risks inherent in adopting technology, and communication with other directors (Alkrdem, 2014); and level in the chain of command of leadership in distributing responsibilities (Divaharan & Lim, 2010; Hulpia & Devos, 2010).…”
Section: Theoretical Backgroundmentioning
confidence: 99%